An integrated approach for the numerical modeling of severely damaged historic structures: Application to a masonry bridge. (January 2021) - Pepi, Chiara; Cavalagli, Nicola; Gusella, Vittorio; Gioffrè, Massimiliano
Highlights: An integrated approach to assemble and update accurate Finite Element models is presented The proposed methodology is applied to a severely damage masonry arch bridge Fully non destructive experimental activities are carried out The results derived by accurate and simplified numerical models are compared Effects of geometric irregularities on the modal properties are discussed Abstract: This paper presents an integrated approach that combines advanced survey procedures, such as close range photogrammetry based on high resolution images provided by Unmanned Aerial Vehicles, and Ambient Vibration Tests to develop accurate Finite Element models of severely damaged historic masonry structures. The proposed methodology is applied to a masonry arch bridge located in Todi, Central Italy, characterized by severe damage conditions involving diffuse material degradation and structural damages. Two numerical models are developed starting from the digital geometric survey: the first accurately describes the irregular actual geometry due to damage; the second regularizes the boundary surfaces as standard procedure in common practice when detailed survey is not available. The crucial role of the geometric irregularities given by the severe damage state on the dynamic properties of the masonry bridge is demonstrated by comparing the modal parameters of the two models. Furthermore, sensitivity analysis is carried out in order to assess the combined effect of different mechanical characteristics and geometric configurations on the modal properties and to select suitable updating parameters. The overall methodology is completed by a final model updating procedure targeting the experimental modal parameters estimated from Ambient Vibration Tests.